Hermeneutics of liberation from Mesoamerica: Listening to the Voice of the Jungle - Mena Oreamuno, Francisco (2023)
A social position is proposed to carry out a biblical reading where the Caribbean, as a vital space, of the worlds that embrace its waters, is included. Croatto called this exercise eisegesis and proposed this concept as a way to bring liberation struggles into exegesis. The point is that many of the issues that are pressing for the Latin American and Caribbean communities have no reference in the Bible, one of those issues is the wealth of life that nourishes us. To think of the Bible is to think of the desert and sometimes the waters of the Mediterranean (especially the Acts of the Apostles). But the Bible does not know the jungle, it knows the desert, but not the thicket of mountain life. For this reason, and making a series of clarifications to build this position, we conclude with three great metaphors: the tangle, symbiosis and putrefaction.